Electric vehicles adoption challenges in Oman: a comprehensive assessment and future prospects for sustainable cities - Ahmed, Umar; Fida, Bashir Ahmad; Thumiki, Venkat Ram Raj; Hamdun Al Marhoobi, Sauda Salim (Frontiers in Sustainable Cities, 2024)
This study aims to investigate public perceptions of obstacles to Electric Vehicle (EV) adoption in Oman and assess the impact of EVs on cities' sustainability. A survey was conducted, and questionnaires were distributed to over 300 car consumers residing in the Muscat governorate. The questionnaire was designed using Microsoft Forms and distributed to the respondents using email and social media platforms like WhatsApp, face-book, LinkedIn, Instagram, etc. Descriptive statistics and Structural Equation Modeling (SEM) were used for data analysis. The study's findings reveal that the lack of public charging infrastructure, limited knowledge about EVs, and the suitability of available EV models are the major obstacles to adopting EVs in Oman. While safety apprehensions, financial considerations, and limited public awareness of climate change impact are other barriers. The SEM results reveal a strong positive correlation between the costeffectiveness of EVs and the intention to purchase, the availability of public charging infrastructure and the intention to adopt EVs, awareness of the impact of climate change, and the intention to embrace EVs. Nevertheless, there is a negative relationship between the safety concerns of EVs and the intention to buy EVs. Regarding the impact of EVs on Oman's cities, respondents generally believe in the potential for EVs to improve air quality, enhance urban living conditions, and mitigate noise and air pollution. However, the respondents were also cautious about the widespread use of EVs due to the high infrastructure investment costs and energy consumption. Therefore, the study suggests targeted interventions such as robust public awareness campaigns, improved charging infrastructure, and incentives for EV adoption. These insights are valuable for policymakers, industry stakeholders, and advocacy groups aiming to overcome barriers and leverage perceived benefits. The study offers essential insights into the evolving global landscape of electric mobility, guiding and promoting a sustainable and widespread adoption of electric vehicles in Oman.